THE EFFECT OF CAKE USAGE AS MOBILE ASSISTED LANGUAGE LEARNING ON STUDENTS’ ENGLISH SPEAKING SKILL IN SMP HANG TUAH 1 BELAWAN - Ani Deswita Chaniago (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
This research aims to analyze the effect of Cake usage on students’ English speaking skill in SMP Hang Tuah 1 Belawan. This research was a quantitative research. The research sample were 67 students. The research instruments were a questionnaire and interview with the teacher and students. The data was analyzed by T-Test and Coefficient of Determination to know the effect of X variable on Y variable. The research results on the questionnaire found that from T-Test, it showed Sig. value 0,0000 was lower than 0,05 and TScore 19,101 was higher than TTable 1,668. From Coefficient of Determination, it showed that 84,9% of Cake usage effected the improvement of students’ English speaking skill in SMP Hang Tuah 1 Belawan. The research results on the interview found that both of the teacher and students agreed that Cake is a very usefull, interesting, motivating and supporting learning media to promote students’ improvement to speak English more confident than before.